SEBARAN GUA PENGUBURAN DI KABUPATEN KONAWE KEPULAUAN PROVINSI SULAWESI TENGGARA - Mando Maskuri (SANGIA JOURNAL OF ARCHAEOLOGY RESEARCH, 2017)
The formulation of the problem in this study is, 1) Any burial caves in Konawe Islands, SoutheastSulawesi Province. 2) How is the distribution of burial caves in Konawe Islands,Southeast Sulawesi Province. 3)What factors are behind the selection and utilization of burial caves in Konawe Islands, Southeast SulawesiProvince. With Objective 1) To identify burial cave sites in Konawe Islands, Southeast Sulawesi Province. 2) Toidentify the distribution of burial cave sites in Konawe Islands, Southeast Sulawesi Province. 2) To explain thefactors behind the selection and utilization of burial caves in Konawe Islands, Southeast Sulawesi Province. The results of this study are 1) The number of burial cave sites in the study area are 9 sites, amongothers, Kontara 1 Cave, Kontara 2 Cave, Ceruk Kaheng Kalua 1, Ceruk Kaheng Kalua 2, Ceruk Kaheng Kalua 3,Kaheng Kalua Ceruk 4, Kaheng Kalua Cave, Dompo-Dompo Cave and Subandri Cave. 2) Distribution of burialcave sites in the study area is divided into two regions, namely the three sites, namely Kontara Cave 1 KontaraCave Subandri Cave site and 6 coastal sites, Ceruk Kaheng Kalua 1, Ceruk Kaheng Kalua 2, Kaheng KaluaCeruk 3, Ceruk Kaheng Kalua 4, Kaheng Cave Kalua, Dompo-Dompo. 3) The underlying factors in choosing thelocation of burial are among others. The height of a place, slope, landform, and river.